2021
DOI: 10.1108/jmlc-07-2021-0070
|View full text |Cite
|
Sign up to set email alerts
|

The preferred type of financial intelligence for early detection of terrorist financing activities

Abstract: Purpose This paper aims to inform the readers about the preferred type of financial intelligence for early detection of terrorist financing activities. Design/methodology/approach Literature review methodology was adopted to find the existing approaches of financial intelligence and logical reasoning was applied to sort out what type of financial intelligence is more preferable for early detection of terrorist financing activities. Findings It was found that proactive financial intelligence executed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Moreover, the impact of green finance and financial intelligence in combating terrorism financing is also a critical area of study, as indicated by (Falcone & Sica, 2019), (Gowhor, 2021), and (Ünal & Altun, 2020). These studies emphasize the role of financial intelligence and green finance in addressing long-term investment needs and early detection of terrorist financing activities, which are pertinent to the finance sector.…”
Section: Case Studiesmentioning
confidence: 99%
“…Moreover, the impact of green finance and financial intelligence in combating terrorism financing is also a critical area of study, as indicated by (Falcone & Sica, 2019), (Gowhor, 2021), and (Ünal & Altun, 2020). These studies emphasize the role of financial intelligence and green finance in addressing long-term investment needs and early detection of terrorist financing activities, which are pertinent to the finance sector.…”
Section: Case Studiesmentioning
confidence: 99%